Ethical Leadership in Information Technology Decision Making and its Impact on Risk Management - Purwo Agus Sucipto; Maria Jashinta Elisabet Hamboer; Nazaruddin Ahmad; Zakaria Satrio Darmawan; Filda Angellia (Jurnal Minfo Polgan, 2023)
In the rapidly growing digital era, information technology has become an integral part of almost all aspects of our lives, including in the world of business and management. Appropriate and effective use of information technology is the key to achieving competitive advantage in today's competitive business environment. However, making decisions related to information technology is not an easy task, as information technology is often complex and high-risk. The purpose of this study is to analyse ethical leadership in information technology-related decision making and its impact on risk management. The method used is a qualitative literature review that focuses on an in-depth understanding of the topic in the time span from 2006 to 2023. The main objective of this method is to identify, analyse, and synthesise relevant scientific literature that has been published in various journals, conference papers, and other academic sources accessible through Google Scholar. The study results show that ethical leadership plays a central role in ensuring that IT-related decisions are taken with ethical principles in mind and with the aim of minimising risk. Ethical leadership contributes to the avoidance of data misuse, creating a culture of transparency and accountability, ensuring fair use of technology, and being mindful of the impact of IT decisions on society and the environment.